HE SEPHARDI DIASPORA IN COCHIN, INDIA - Nathan Katz and Ellen S. Goldberg (Jewish Political Studies Review, 1993)
The influx of Sephardim into the ancient Jewish community of Cochin, in south India, resulted in a pattern of social organization unique in the Jewish world: the infamous white Jew/black Jew/brown Jew system. The Jews of Cochin organized themselves in patterns derived from their Hindu social context, a system known in the West as the caste system. The "white" or Paradesi ("foreign") Jews were Sephardi immigrants together with a few Jews from Iraq, Europe and Yemen, who joined with an indigenous elite. The "black" Jews, better known as Malabari Jews, were an ancient community which may have originated at the time of the destruction of the Second Temple. Each of these groups were slave-holders, and manumitted slaves fmeshuchrarim) from the Paradesi community were commu called "brown" Jews, while manumitted slaves from the Malabari were the known orumakers. (local term, nity by Malayalam language) Paradesi Jews would not count any of the other groups for their minyan, would not allow them synagogal honors, would not marry them, and would not eat meat slaughtered by their ritual slaughterers. Ever since the 1520 responsa by the eminent Sephardi halakhist Rabbi ibn Zimra, foreign Jews had been unanimous in condemning this discrimi natory behavior, and Paradesi Jews in Cochin had been uniform in ignoring these admonitions. Yet while Indian culture may have been the source of the problem, it was also the inspiration for its solution. A.B. Salem, known as the "Jewish Gandhi" 98 led sit-ins, hunger strikes, and other forms of "civil disobedience" an end only (satyagr